Novel Treatment for Mantle Cell Lymphoma including Therapy-resistant Tumor by NF-κB and mTOR Dual Targeting Approach - Chaturvedi, Nagendra K. (2013)
Mantle cell lymphoma (MCL) is one of the most aggressive B cell non-Hodgkin lymphomas with a median survival of about five years. Currently, there is no curative therapy available for refractory MCL because of relapse from therapy-resistant tumor cells. The NF-κB and mTOR pathways are constitutively active in refractory MCL leading to increased proliferation and survival. Targeting these pathways is an ideal strategy to improve therapy for refractory MCL. Therefore, we investigated the in vitro and in vivo antilymphoma activity and associated molecular mechanism of action of a novel compound 13-197, a quinoxaline analog that specifically perturbs IκB kinase (IKK) β, a key regulator of the NF-κB pathway. 13-197 decreased the proliferation and induced apoptosis in MCL cells including therapy-resistant cells compared to control cells. Furthermore, we observed down-regulation of IκBα phosphorylation and inhibition of NF-κB nuclear translocation by 13-197 in MCL cells. In addition, NF-κB regulated genes such as cyclin D1, Bcl-XL and Mcl-1 were down-regulated in 13-197-treated cells. 13-197 also inhibited the phosphorylation of S6K and 4E-BP1, the downstream molecules of mTOR pathway that are also activated in refractory MCL. Further, 13-197 reduced the tumor burden in vivo in the kidney, liver, and lungs of therapy-resistant MCL bearing NOD-SCID mice compared to vehicle treated mice; indeed, 13-197 significantly increased the survival of MCL transplanted mice. Together, results suggest that 13-197 as a single agent disrupts the NF-κB and mTOR pathways leading suppression of proliferation and increased apoptosis in malignant MCL cells including reduction in tumor burden in mice.